Simple model of evapotranspiration by Eucalyptus plantations for data poor areas and tested using water balance data from a small catchment in Guangxi, China. (15th May 2019) - Ren, S.; White, D. A.; Xiang, D.; Short, T. M.; Xiao, W.; Chen, J.; Deng, Z.; Yang, Z.
ABSTRACT: Measurements of catchment and stand water balance were made in a small, upland catchment in Guangxi province, China that was covered with a plantation of a Eucalyptus urophylla × Eucalyptus grandis hybrid. These data were used to investigate the relationship between streamflow and the net stand water balance and to test the efficacy of a relationship between the crop factor (ratio of evapotranspiration to potential evaporation) and relative plant available soil water for predicting evapotranspiration. The model was then used to quantify the effect of afforestation with Eucalyptus plantations on the water balance of (1) upland catchments with shallow soils and (2) catchments with deeper soil profiles such as those that can occur in lowland catchments in Guangxi. During the experiment, the plantation experienced a dry year in 2014, when rainfall was 1095 mm, and a year with approximately average rainfall in 2015 (1493 mm). In 2014, plantation evapotranspiration was 779 mm or 71% of rainfall while during 2015 the annual plantation evapotranspiration was 931 mm or 61% of rainfall. Measured streamflow for a full year was only 18 mm (2%) less than the difference between rainfall and estimated evapotranspiration. The relationship between measured streamflow and the net stand water balance was also strong (r 2 = 0.8) and unbiased (slope of 1.006). A model that predicted the crop factor as a function of relative plant available soil water explained more than 78% of the variation in observed evapotranspiration and had a model efficiency of 0.73. It also provided an unbiased prediction of monthly evapotranspiration. When used to model the effect of a change from grassland to a plantation of E. urophylla, it predicted an average annual decrease in drainage of 70 mm and a 5% increase in the number of months with zero flow.